Central Nervous System Sarcoidosis: A National-Based registry study - Al-Zamer, Yazan; Al-Horani, Sami; Akhdar, Marah; Majali, Ghaydah; Alzghoul, Hamza; Younis , Moustafa; Ameli, Pouya; Alzghoul , Bashar (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Sarcoidosis of the central nervous system (CNS) often presents deleterious effects on affected patients. Data and available literature discussing the diagnosis and treatment of this condition are scarce and inconsistent. In this study, we aim to shed light on demographics, management, diagnostics, and clinical complications of CNS sarcoidosis patients within the United States (US) based on a nation-wide registry questionnaire. Methods: Our retrospective study was conducted based on a national registry investigating 3,835 respondents to the Foundation for Sarcoidosis Research Sarcoidosis Advanced Registry for Cures Questionnaire (FSR-SARC). This national registry data was collected during the period of June 2014 to August 2019. We performed propensity score matching, summary, univariate, and multivariate analyses to establish a comparison between the presence and absence of central nervous system sarcoidosis. Results: We identified a total of 420/3634 (11.55%) patients having CNS sarcoidosis; 296 (70.5%) were females, 307 (73.1%) were Caucasian and 81 (19.3%) were African American. The mean (±SD) age at diagnosis of CNS sarcoidosis was 43.3 (±12) years old. Multiorgan involvement (≥3 organs) was present in 318/420 (75.7%) patients. Brain magnetic resonance imaging was the most common ancillary diagnostic modality used and reported to be abnormal 251/328 (76.5%). Corticosteroids were the most used treatment by CNS sarcoidosis patients 206/420 (49.0%) followed by cytotoxic agents 180/420 (42.9%). Conclusions: CNS sarcoidosis prevalence in our cohort was similar to what has been described previously. The most prevalent imaging modality used was cranial MRI. Corticosteroids were the most used medications. Lastly, CNS sarcoidosis showed a propensity to cause several clinical complications such as chronic pain syndrome and disability.